Receiving and Storage Process Analysis Raw Materials using Check Sheet Method and Fishbone Diagram - Kumalasari, Ika Dyah; Wahyudi, Maulidya Eka (Journal of Agri-Food Science and Technology, 2024)
Raw materials are very important to make sure finished product have a good quality or as the standard Company. Storage of raw materials can cause physical and chemical damage as well as the development of microorganisms and shorten the shelf life of materials. The method of data collection is done by collecting primary data in the form of observations, interviews and documentation. Secondary retrieval in the form of literature study which is then carried out the problem-solving analysis in the form of check sheets and fishbone diagram. Raw material was compared the company's standards with SNI regarding the quality requirements of arrowroot starch. The results show that the main cause of non-compliance with the company's SOP comes from humans. It can be concluded that the incoming raw materials are weighed and quality checked by QC by storage of raw materials by the storage criteria of each raw material including temperature, storage time, room and storage position. At the same time, we have measures accident which have greater occurrence probability to eliminate the risk of rejected product.